Survival Strategies of Finnish SMEs in the Time of Global Crisis - Saarenketo Sami; Kuivalainen Olli; Torkkeli Lasse; Isotalo Akseli; Myers Alexander (Edward Elgar Publishing, 2022)
The onset of the COVID-19 pandemic has resulted in a crisis that has impacted international business and entrepreneurship globally. Many small- and medium-sized enterprises (SMEs) have been particularly hard hit, yet many are also finding strategies to survive and even thrive in this “new normal”.  This chapter highlights the survival strategies of SMEs in the small open economy context of Finland where, alike most European countries, international trade has been restricted due to the pandemic. We conduct a qualitative case analysis of five Finnish SMEs across different industry sectors, describing the internal and external changes they have undergone during the crisis, and we also shed light on the strategies and contingency planning they have been employing in order to survive. From the results, it is evident that internationalization remains an opportunity for Finnish SMEs. We conclude the chapter by summarizing our recommendations for SMEs dealing with the current and the next crisis, while also considering the generalizability of those recommendations in environments less stable and developed as the Finnish context.
Small and Medium Sized Enterprises and the COVID-19 Response